2015
DOI: 10.2994/sajh-d-14-00040.1
|View full text |Cite
|
Sign up to set email alerts
|

The Black Sea Turtle (Chelonia mydas agassizii) at Lobos de Tierra Island, Northern Peru: High Densities in Small Areas

Abstract: Preliminary findings regarding black turtle (Chelonia mydas agassizii) occurrence in Lobos de Tierra Island, Northern Peru showed that 95% and 5% of turtles were juveniles and sub-adults, respectively, with an overall mean curved carapace length of 57.5 ± 7 cm (26.0-74.4 cm, n = 199). A total mean density of 180.4 turtles/km 2 was found with highest densities found in bays and inlets located in the southeast. Inshore densities in shallow waters (< 1.5 m) were almost one order of magnitude greater than offshore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
1
7
0
7
Order By: Relevance
“…It is also interesting to note that the measurement of the carapace (SCL: 50.2 cm) of our specimen was a juvenile [8,36,37], just like the specimen (SCL: 47 cm) reported at Desolation Island [23]. These measures would be in line with the life stage reported for feeding areas in Peru [38,39] and with the available size of measured specimens in Chilean waters (SCL mean: 49 cm; [14]), indicating that most are juveniles or subadult individuals.…”
Section: Discusionsupporting
confidence: 79%
“…It is also interesting to note that the measurement of the carapace (SCL: 50.2 cm) of our specimen was a juvenile [8,36,37], just like the specimen (SCL: 47 cm) reported at Desolation Island [23]. These measures would be in line with the life stage reported for feeding areas in Peru [38,39] and with the available size of measured specimens in Chilean waters (SCL mean: 49 cm; [14]), indicating that most are juveniles or subadult individuals.…”
Section: Discusionsupporting
confidence: 79%
“…The feeding ecology of this species has been studied throughout most of its distribution (Quiñones et al, 2015a). At their juvenile developmental habitats, green turtles can take on a herbivorous diet, feeding primarily on seagrass and algae (Plotkin et al, 1993;Seminoff et al, 2002aSeminoff et al, , 2003López-Mendilaharsu et al, 2005;Sampson & Giraldo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have noted that C. mydas juveniles can also be carnivorous consumers, foraging mainly on cnidarians (Carrión-Cortez et al, 2010), sponges (Seminoff et al, 2002b), and tunicates (Amorocho & Reina, 2007. Additional studies have also identified an omnivorous diet, based mainly on algae but with an additional wide variety of animals, such as crustaceans, fish eggs, mollusks, and, to a lesser extent, jellyfish (Hays-Brown & Brown, 1982;De Paz et al, 2004;Kelez et al, 2004;Santillán, 2008;Quiñones et al, 2015aQuiñones et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations